2021
DOI: 10.1002/hbm.25369
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic power of resting‐state fMRI for detection of network connectivity in Alzheimer's disease and mild cognitive impairment: A systematic review

Abstract: Resting‐state fMRI (rs‐fMRI) detects functional connectivity (FC) abnormalities that occur in the brains of patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI). FC of the default mode network (DMN) is commonly impaired in AD and MCI. We conducted a systematic review aimed at determining the diagnostic power of rs‐fMRI to identify FC abnormalities in the DMN of patients with AD or MCI compared with healthy controls (HCs) using machine learning (ML) methods. Multimodal support vector machi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 78 publications
2
72
1
Order By: Relevance
“…In future studies, a larger sample should be collected, and the number of subjects balanced as the scale of the ADNI database is expanding ( Aisen et al, 2010 ). Furthermore, future studies should attempt to explore different methods of classification in different stages of AD, including the interpretability of structural and functional brain abnormalities ( Ibrahim et al, 2021 ). The versatility in multiple data sets will be necessary to validate the robustness of the models.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, a larger sample should be collected, and the number of subjects balanced as the scale of the ADNI database is expanding ( Aisen et al, 2010 ). Furthermore, future studies should attempt to explore different methods of classification in different stages of AD, including the interpretability of structural and functional brain abnormalities ( Ibrahim et al, 2021 ). The versatility in multiple data sets will be necessary to validate the robustness of the models.…”
Section: Discussionmentioning
confidence: 99%
“…The most well-established finding is that hippocampal–default mode network (DMN) connectivity is reduced compared with healthy people ( Hohenfeld et al, 2018 ). Among the nodes within the DMN, the importance of connectivity between the precuneus and PCC has been demonstrated in numerous studies ( Greicius et al, 2003 ; Wu et al, 2011 ; Teipel et al, 2015 ; Palmqvist et al, 2017 ; Ibrahim et al, 2021 ). The precuneus plays a central role in visuospatial imagery, episodic memory retrieval, and processing of self-related information ( Cavanna and Trimble, 2006 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Standard brain models, such as the Montreal Neurological Institute 152 nonlinear 6th Generation Stereotaxic Registration Model, provide a population-based template for brain anatomy (MNI space template) that is widely used in neuroimaging for registering information across participants into a common coordinate system (MNI space) (Grabner et al, 2006;Evans et al, 2012). Functional neuroimaging studies have identified functional alterations in vivo, quantifying correlated activity in networked cortical regions of the brain, or "functional connectivity, " and how that connectivity changes with disease (Ibrahim et al, 2021). These analyses have revealed how specific networks may be selectively vulnerable to specific neurodegenerative processes, and demonstrated that diseases such as AD can selectively impair systems of cortico-cortical connectivity (Raichle et al, 2001;Buckner et al, 2009;Seeley et al, 2012;Dai et al, 2015;Jones et al, 2016).…”
Section: Introductionmentioning
confidence: 99%